The Lessons of the Living Dead: Marcel's Journey from Balbec to Douville-Féterne in Proust's Cities of the Plain: Part Two - Jonathan Warren (Studies in 20th & 21st Century Literature, 1995)
By analyzing the narrative of Marcel's journey by the "little train" from Balbec to Douville-Féterne the essay engages with the Proust criticism of Georges Poulet, Paul de Man, and Julia Kristeva to support Hayden White's claim that "it is legitimate to read Proust's narrative as an allegory of figuration itself." Like the Madeleine episode, this one serves as a point from which retrospection and prospection radiate. Central to the discussion is the description of Verdurins' dinner party guests as they stand ready to board the train on the platform at Graincourt: their vivacity, compared to a sort of extinction, suggests a chiasmus between life and death, past and present, experience and reading, and phenomenon and figuration that enriches and integrates Poulet's phenomenological glosses, de Man's rhetorical analysis, and the Kristevan approach to Proust's text. In close proximity to the Verdurins' guests, Marcel is struck chiefly by their remoteness, their pastness, their distance: the figural and phenomenal instability of space and time finally converge in Marcel himself as Proust effects a biblical joke.
Keywords: Marcel' s journey; Proust; little train; Balbec; Douville-Féterne; Georges Poulet; criticism; Paul de Man; Julia Kristeva; Hayden White; allegory of figuration; allegory; Madeleine episode; Madeleine; retrospection; prospection; Verdurins; dinner party; Graincourt; train; extinction; Chiasmus; life; death; past; present; experience; reading; phenomenon; figuration; Poulet; phenomenological glosses; guests; remoteness; pastness; figural; instability of space and time; space; time; joke; Biblical joke